2004
DOI: 10.1016/j.physe.2003.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the dielectric-constant mismatch and magnetic field on the binding energy of hydrogenic impurities in a spherical quantum dot

Abstract: Within the effective mass approximation and variational method the effect of dielectric constant mismatch between the size-quantized semiconductor sphere, coating and surrounding environment on impurity binding energy in both the absence and presence of a magnetic field is considered. The dependences of the binding energy of a hydrogenic on-center impurity on the sphere and coating radii, alloy concentration, dielectric-constant mismatch, and magnetic field intensity are found for the

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 34 publications
(50 reference statements)
0
3
0
1
Order By: Relevance
“…Effects of external environments such as a magnetic field [11][12][13][14][15][16][17][18][19][20][21][22], an electric field [23][24][25][26], both electric and magnetic fields [27,28] and hydrostatic pressure [29] on the electronic and optical properties of the nanostructure systems with impurities located on or out from the center constitute a subject of considerable interest of theoretical and experimental studies. Recently, many investigations both theoretical and experimental have been carried out on the energy levels and binding energies of hydrogenic impurities in the presence of a magnetic field using diverse calculation methods such as perturbation, variational and finite-difference methods [30][31][32]. As general outcome observations, these electronic properties depend strongly on the external perturbations, potential barrier, size and shape of the structures.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of external environments such as a magnetic field [11][12][13][14][15][16][17][18][19][20][21][22], an electric field [23][24][25][26], both electric and magnetic fields [27,28] and hydrostatic pressure [29] on the electronic and optical properties of the nanostructure systems with impurities located on or out from the center constitute a subject of considerable interest of theoretical and experimental studies. Recently, many investigations both theoretical and experimental have been carried out on the energy levels and binding energies of hydrogenic impurities in the presence of a magnetic field using diverse calculation methods such as perturbation, variational and finite-difference methods [30][31][32]. As general outcome observations, these electronic properties depend strongly on the external perturbations, potential barrier, size and shape of the structures.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors investigated the properties of hydrogenic impurities in SQDs [11][12][13][14][15][16][17][18][19]. In addition, external perturbation such as application of an electric and magnetic field can provide valuable information [20][21][22]. They found that the impurity binding energy depends strongly on impurity position and magnetic field strength.…”
Section: Introductionmentioning
confidence: 99%
“…In the geometrical respect, the simplest systems are spherical QD which are researched in a lot of work (e.g., Refs. [3][4][5][6][7]). However, they possess one geometrical parameter-radius, by means of which it is possible to manipulate energy levels of charge carriers.…”
Section: Introductionmentioning
confidence: 99%